2017
DOI: 10.1007/s00299-017-2152-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic nucleolar activity in wheat × Aegilops hybrids: evidence of C-genome dominance

Abstract: NOR loci of C-subgenome are dominant in wheat × Aegilops interspecific hybrids, which may have evolutionary implications for wheat group genome dynamics and evolution. After interspecific hybridisation, some genes are often expressed from only one of the progenitor species, shaping subsequent allopolyploid genome evolution processes. A well-known example is nucleolar dominance, i.e. the formation of cell nucleoli from chromosomes of only one parental species. We studied nucleolar organizing regions (NORs) in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In synthetic allotetraploid wheat both sets of parental NORs were expressed just after hybridization, but one parental NOR was immediately silenced after chromosome doubling (Guo and Han, ). C‐subgenome NOR loci were dominant in wheat × Aegilops interspecific hybrids (Mirzaghader et al ., ). In addition, Guo and Han () reported that allopolyploidization was a critical step for NOR silencing that could not be reversed by haploidization in wheat.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In synthetic allotetraploid wheat both sets of parental NORs were expressed just after hybridization, but one parental NOR was immediately silenced after chromosome doubling (Guo and Han, ). C‐subgenome NOR loci were dominant in wheat × Aegilops interspecific hybrids (Mirzaghader et al ., ). In addition, Guo and Han () reported that allopolyploidization was a critical step for NOR silencing that could not be reversed by haploidization in wheat.…”
Section: Discussionmentioning
confidence: 97%
“…The copy number of rRNA genes in wheat ‘Chinese Spring’ (CS) has been estimated to be 9150; most of these (60%) are located on 6B ( Nor‐B2 ), with approximately 30% on 1B ( Nor‐B1 ) and the remaining 10% on several chromosome arms, as estimated from signal intensities in hybridization studies (Flavell and O'Dell, ). Nucleolar dominances were observed in several interspecific hybrids between species in the tribe Triticeae (Neves et al ., ; Guo and Han, ; Mirzaghader et al ., ). However, the genomic architecture of NORs in wheat and their sequence‐based analysis, including gene expression, remain unexplored because most previous studies on NORs in wheat and related species were based on cytological techniques such as silver staining and fluorescent in situ hybridization (FISH).…”
Section: Introductionmentioning
confidence: 97%
“…Consistent with a largely stochastic process, species of D‐genome lineage show differential retention and loss of specific NOR loci from progenitors. Reorganization of NOR loci has been commonly reported in interspecific hybrids (Pikaard, ) and recent work highlighted hierarchical nucleolar dominance among current wild wheats (Mirzaghaderi et al , ). Much remains to be understood regarding the molecular underpinnings as well as the evolutionary consequences of such chromosome‐scale reorganization.…”
Section: Hybrid Speciation and Chromosome Restructuring In Wild Wheatmentioning
confidence: 94%
“…Subgenome dominance is an important phenomenon in allopolyploids, it was also observed in the interspecific hybrids. For example, in the interspecific hybrids (wheat × Aegilops ), C-subgenome nucleolar organizing regions loci are dominant [ 46 ]. In addition, the subgenome dominance occurred instantly following the hybridization [ 47 ].…”
Section: Discussionmentioning
confidence: 99%